Skill development using interdisciplinary problem solving in a natural resources capstone course. Issue 1 (11th May 2022) - Anderson, Zach D.; Hargiss, Christina L. M.; Norland, Jack E.
Abstract: Postsecondary curriculum is designed to prepare students for their careers following graduation, which traditionally revolves around technical aspects of their respected career field. Capstone courses were introduced to help ease students' transition from the university into their careers. However, little research containing empirical evidence exists on the effectiveness of capstone courses in natural resources. This study evaluated 6 yr of course graduates from an interdisciplinary problem‐solving capstone course in natural resources, seeking to understand the skills gained and what portions of the course were most useful in transitioning students to their future careers. Results show the course was able to enhance students' writing, communication, job preparation, and teamwork skills. Students valued knowledge gained on soft skills, such as communication and teamwork, over technical skills specific to their major. Overall, the students valued the interdisciplinary problem solving nature of the course, as most natural resource issues are interdisciplinary. Areas that could be improved in this capstone model were focused on improving individual student's verbal communication and presentation skills. Information from this study is useful to colleges and universities considering and using capstone courses to determine skills that can be taught and to determine if using real world problems in an interdisciplinary setting in their courses would be beneficial. Core Ideas: Real‐world problem solving in an interdisciplinary setting enhanced skill development. Participants reported enhanced communication, critical thinking, and problem‐solving skills. Presentation and delivery of verbal communication skills could be further enhanced. Participants valued soft skills, such as communication, as much or more than technical skills. The majority of students learned most of their job preparation skills in the capstone course.